Community-Based Health Insurance Utilization and Its Associated Factors among Rural Households in Akaki District, Oromia, Ethiopia, 2021 - Amenti Teka Geferso; Sisay Begashaw Sharo (Hindawi Limited, 2022)
Background. Community-based health insurance is widely recognized as the most effective way to achieve universal health coverage (UHC) with adequate financial protection against healthcare costs, to promote equal access to high-quality healthcare, increase financial security, and enhance social cohesion and solidarity. Objective. The objective of this study was to determine community-based health insurance utilization and its associated factors among rural households in Akaki District, Oromia special zone surrounding Finfinnee, Oromia, Ethiopia, in May 2021. Methods and Materials. A community based cross-sectional study was conducted on 600 households in May 2021. A multistage sampling technique was used to select households. Data were collected using pretested and standardized questionnaires entered into Epi Info version 7.2.4 and analyzed using SPSS version 26. Bivariate and multivariate logistic regressions were computed to identify the factors associated with community-based health insurance utilization. A P value <0.05 with 95% CI was used as a cut-off point to declare the level of statistical significance. Results. The magnitude of community-based health insurance (CBHI) utilization was 398 (66.3%) (95% CI: 0.63, 0.70). In the multivariate logistic regression analysis, the odds of CBHI utilization for males were 2 times higher (AOR = 1.629; 95% CI: 1.063, 2.497) compared to female-headed households; household family size <5 was 3 times higher (AOR = 2.99; 95% CI: 1.987, 4.139) compared to household family size >5; farmer was 4 times higher (AOR = 3.763; 95% CI: 1.371, 10.327) compared to other occupational status; household income <30,000 ETB was 2 times higher (AOR = 2.474; 95% CI: 1.514, 4.043) compared to the household income of 30000 ETB, and all these were factors significantly associated with CBHI utilization. Conclusion. The magnitude of CBHI utilization was low (66.3%) compared to the HSTP II target (80%) and other studies. The results of the study showed that age, sex, household family size, household income, and trustworthiness were among the factors significantly associated with community-based health insurance utilization.